Genome-wide and pan-genomic analysis reveals rich variants of NBS-LRR genes in a newly developed wild rice line from Oryza alta Swallen - Shivute, Fimanekeni Ndaitavela; Zhong, Yi; Wu, Jinwen; Bao, Yueming; Wang, Wei; Liu, Xiangdong; Lu, Zijun; Yu, Hang (Frontiers in Plant Science, 2024)
Introduction Oryza alta Swallen is an allotetraploid perennial wild rice and contains CCDD genome, which may harbor favorable genes for the enrichment of genetic resource. Methods A new wild rice line, Huaye 5, was developed from Oryza alta Swallen in our lab. Whole genome re-sequencing and pan-genomic analysis were employed to analyze its genomic variations and novel genes. Results and Discussion More than ten million genomic variations were detected when compared with Asian cultivar. Among the variational genes, 724, 197 and 710 genes coded protein kinase, synthetase and transcription factor, respectively. A total of 353, 131 and 135 variational genes were associated with morphological trait, physiological trait, resistance or tolerance, respectively. A total of 62 were NBS-LRR genes were detected, in which 11 NBS-LRR genes expressed in sheath and mature stem, and 26 expressed in young and mature roots expressed. The pan-genome sequences of wild rice species with CCDD genome were constructed by integrating 8 Oryza alta (OA), 2 Oryza grandiglumis (OG) and 18 Oryza latifolia (OL) accessions. A total of 28 non-reference NBS-LRR genes were revealed, and 7 of which were mainly expressed in mature roots. This research demonstrated rich DNA variation in the Oryza alta Swallen that may provide a new germplasm for rice resistance breeding.